ARAHAN PRODUK PARIWISATA BERBASIS MASYARAKAT LOKAL DI WILAYAH PERDESAAN - Adikampana, I Made; Sunarta, I Nyoman; Kusuma Negara, I Made (Jurnal IPTA (Industri Perjalanan Wisata); Vol 5 No 2 (2017): Jurnal IPTA (Desember 2017)DO - 10.24843/IPTA.2017.v05.i02.p02, 2018)
This paper addressed the process of the development of community-based rural tourism products in Pinge Tourism Village. Community-based rural tourism products are acknowledged as a tourist attraction in rural areas created by local communities be based on the tourism resources that possess by communities themselves. Pinge Tourism Village has a various of tourism resources that can be developed as a local community-based rural tourism product. From the inside of the physical environment resources to the diversity of social and cultural heritage. In adaptation with the mapping of tourism resources, can be determined the themes of development of community-based rural tourism products. There are four themes that can be considered for the development of community-based rural tourism products in Pinge Tourism Village, specifically spiritual routine, agricultural routine, gastro-cultural routine, and communal routine. These four themes further form the basis for determining community-based rural tourism products or special interest tourism activities of traditional villages in Pinge Tourism Village. There are several guidelines for the development of community-based rural tourism products that can be developed in Pinge Tourism Village such as spiritual tourism, agritourism, culinary tourism, and rural nightlife attraction.